MARSSONINA LEAF BLOTCH ON THE APPLE ORCHARD IN BATU, INDONESIA - Ika Rochdjatun Sastrahidayat; Hery Nirwanto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
In Indonesia, apple orchards are decreasing because of leaf blotch disease. Marssonina leaf blotch has not been widely known and the problems are associated with the incidence of the epidemic so they need to be studied. Research aimed to investigate the biological aspect of Marssonina leaf blotch, the resistance of apple varieties and the alternative host of Marssonina coronaria, and the interactions between Marssonina leaf blotch and weather factors. The research was conducted in laboratory, greenhouse and on apple orchard respectively. There are three results in this research. First, fruit bodies (apothecia) are not produced by fungus, but only conidia (imperfect form) are. Second, based on bioassay, pathogen survives only on the apple. Finally, there are three formula can be used to predict the leaf blotch disease, such as:1) Y=-37.91+19.98X6 (population of spores in the air),2) Y = -438.13 + 25.71X1 (temperature) -3.05X2 (humidity) + 41.07X3(wind speed) -2.07X4 (sunlight) + 19.25X5 (rainfall), and 3) Y = -43.86-1.61 22.60 X5 (rainfall) + X6 (population of spores).